2009
DOI: 10.1038/jhg.2009.16
|View full text |Cite
|
Sign up to set email alerts
|

Screening of 336 single-nucleotide polymorphisms in 85 obesity-related genes revealed McKusick–Kaufman syndrome gene variants are associated with metabolic syndrome

Abstract: Genetic factors are important in the development of metabolic syndrome. However, the genetic background of metabolic syndrome remains unclear. We screened polymorphisms in 85 obesity-related genes to determine which may be associated with metabolic syndrome. A total of 336 single-nucleotide polymorphisms (SNPs) in 85 genes selected from the JSNP database were genotyped. We conducted case-control association analyses using patients with metabolic syndrome (n¼1080) and control individuals (n¼528) who had no risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Of the 150 genes which have been identified with ASD risk factors variants at least 6 relate to BBS. This includes BBS10 which, along with BBS1 , is the gene most frequently mutated in our cohort of patients . In this study, six out of seven of our patients with BBS10 mutations and four out of five with BBS1 mutations had significant ASD symptoms.…”
Section: Discussionmentioning
confidence: 56%
“…Of the 150 genes which have been identified with ASD risk factors variants at least 6 relate to BBS. This includes BBS10 which, along with BBS1 , is the gene most frequently mutated in our cohort of patients . In this study, six out of seven of our patients with BBS10 mutations and four out of five with BBS1 mutations had significant ASD symptoms.…”
Section: Discussionmentioning
confidence: 56%
“…All these three variants carry the risk allele. Abnormal waist circumference (134 cm): The deleterious variant rs1919128 (C2orf16) is associated with the bivariate trait of waist circumference—triglycerides (WC-TG) [31] , and rs1545 (MKKS) is associated with the metabolic syndrome of abdominal obesity [32] . Bronchial asthma: The deleterious variant rs1051931 (PLA2G7) is associated with susceptibility to asthma [33] .…”
Section: Resultsmentioning
confidence: 99%
“…Abnormal waist circumference (134 cm): The deleterious variant rs1919128 (C2orf16) is associated with the bivariate trait of waist circumference—triglycerides (WC-TG) [31] , and rs1545 (MKKS) is associated with the metabolic syndrome of abdominal obesity [32] .…”
Section: Resultsmentioning
confidence: 99%
“…Metabolic syndrome was diagnosed as reported previously. 11,23 In brief, metabolic syndrome is defined by the presence of two or more metabolic abnormalities in addition to obesity (body mass index 425 kg m À2 ). The metabolic abnormalities were as follows: (1) triglyceride level X150 mg per 100 ml and/or high-density lipoprotein cholesterol level o40 mg per 100 ml, or under treatment for this type of dyslipidemia; (2) systolic blood pressure X130 mm Hg and/or diastolic blood pressure blood pressure X85 mm Hg, or under treatment for hypertension; and (3) fasting glucose level X110 mg per 100 ml, or under treatment for diabetes.…”
Section: Study Subjectsmentioning
confidence: 99%
“…3,4 Results from studies using twins and families have suggested that genetic and environmental factors contribute to the clustering of metabolic abnormalities in various ethnic groups. [5][6][7][8][9][10] We determined in a previous study that four single-nucleotide polymorphisms (SNPs) (rs2294901, rs6133922, rs6077785 and rs6108572) in the McKusickKaufman syndrome (MKKS) gene were significantly associated with metabolic syndrome in the Japanese population 11 by screening SNPs in 85 obesity-related genes that had been reported as of 2005. 12 We carried out a large-scale case-control association study and found that secretogranin III (SCG3) 13 and myotubularin-related protein 9 (MTMR9) 14 conferred susceptibility to the obesity phenotype in the Japanese population.…”
Section: Introductionmentioning
confidence: 99%